66 Sudden Death in Wolf-Parkinson-White. Description of Post-mortem Pathological Findings and Clinical Correlates in 19 Cases. (3rd June 2016) - Finocchiaro, Gherardo; Papadakis, Michael; Dhutia, Harshil; Steriotis, Alexandros; Robertus, Jan Lukas; Behr, Elijah; Sheppard, Mary; Sharma, Sanjay
Abstract : Aims: The prevalence of pre-excitation (Wolff-Parkinson-White (WPW) pattern) is estimated at 0.3%. The risk of malignant arrhythmias in asymptomatic individuals is low and ablation of the accessory pathway is considered to diminish the risk of sudden cardiac death (SCD). The aim of the study was to describe clinical characteristics and pathological features of SCD victims with a pre-morbid diagnosis of WPW. Methods: Between 1994 and 2014, 3684 cases of SCD were referred to our cardiac pathology centre; 19 (0.5%) with known pre-excitation on their ECG. Clinical information were obtained from referring coroners. All subjects underwent detailed post-mortem evaluation including histological analysis by an expert cardiac pathologist. Results: The majority of patients were males (n = 16, 84%) of Caucasian descent (n = 17; 89%). The mean age was 31 ± 15 years (2 patients over the age of 50). Five cases (26%) were asymptomatic. Of the 14 symptomatic patients, 13 (68%) reported palpitations, 1 (5%) syncope. Five individuals (26%) had a previous ablation, 4 of which were judged to be successful with resolution of pre-excitation on the ECG. In the majority of cases (n = 15; 79%) SCD occurred at rest. The mean heart weight was 408 ± 105 g. In 10 patients (53%) the post-mortem exam revealed a normal heart, in 5 cases there was a definitive cardiac pathology (n = 4 with hypertrophic cardiomyopathy, n  = 1 with cardiac sarcoid), and 4 cases demonstrated autopsy findings of uncertain significance (n = 2 with idiopathic left ventricular hypertrophy, n = 1 with idiopathic fibrosis, and n = 1 with enlarged left ventricle). Out of the 5 asymptomatic patients, the post-mortem revealed HCM in 3 and a normal heart in 2 cases. The patients that underwent previous ablation were characterized by a normal heart in 3 cases and by idiopathic left ventricular hypertrophy at the post-mortem. Conclusions: One out of four SCD victims was asymptomatic, raising concerns relating to the value of symptoms in risk stratification of individuals with pre-excitation. In addition, accessory pathway ablation did not eliminate the risk of SCD possibly due to multiple pathways. Finally, pre-excitation was associated with additional structural abnormalities in almost 50% of cases, underscoring the necessity of performing baseline echocardiography in all individuals and suggesting that the combination of pre-excitation with additional cardiac pathology may render individuals at higher risk of SCD.